Elite Competition and Economic Reform in Cuba and Vietnam: A Comparative Study of Policy Legitimation - Borja, Anthony Lawrence A. (Animo Repository, 2014)
Cuba and Vietnam, as survivors of the Cold War entered the post-Soviet Era with a myriad of economic woes. These eventually served as incentives for these countries to implement economic reforms that bolstered not only their economic performance, but also the survival of their respective states. However, due to variations in the dynamics of elite competition in these cases, their respective reform programs differed in consistency and their outputs differed in attributes. This is especially true for Cuba and Vietnam wherein the former, initiating market reform programs as early as 1970, experienced two policy reversals during the 80s and the 90s. The latter on the other hand started market oriented reforms on 1981, experienced a failed reversal attempt on 1985 before implementing the Doi Moi reform program of 1986. For this reason, this paper posits the question of what will account for the distinctions (Consistency and Outcome) in the market oriented reform programs of Cuba and Vietnam. Because these cases were sandwiched between pressures coming from economic crises and the legacies of their respective revolutions, this paper contends that the answer lies in the structures that have determined the outcome of elite competition. Thus, this paper argues that the structure of elite competition—that is, the distribution of power that reveals itself through policy legitimation—has defined the consistency and characteristics of market oriented reforms within socialist countries in transition.